1990
DOI: 10.1080/00050069008260005
|View full text |Cite
|
Sign up to set email alerts
|

Professional activities and theoretical orientations of Australian clinical psychologists

Abstract: Professional profiles of Australian clinical psychologists are not widely available, yet such information would seem to be essential in a climate of increasing professional exposure and responsibility. The results of a survey of Australian clinical psychologists are presented. These data establish patterns of professional qualifications, self-reported professional activities, and theoretical orientations of a sample of members of the Clinical Board of the Australian Psychological Society. The findings indicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
13
0

Year Published

1992
1992
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 9 publications
5
13
0
Order By: Relevance
“…A previous paper reported on the findings from a survey of clinical psychologists in Victoria in regard to their employment setting and the nature of their work. Consistent with previous surveys (Byrne & Reinhart, 1990), it was found that Victorian clinical psychologists are most likely to be employed in public health settings, with a smaller proportion engaged in private practice and a minority holding academic positions.…”
supporting
confidence: 85%
See 3 more Smart Citations
“…A previous paper reported on the findings from a survey of clinical psychologists in Victoria in regard to their employment setting and the nature of their work. Consistent with previous surveys (Byrne & Reinhart, 1990), it was found that Victorian clinical psychologists are most likely to be employed in public health settings, with a smaller proportion engaged in private practice and a minority holding academic positions.…”
supporting
confidence: 85%
“…The last examination of the professional practice of Australian clinical psychologists took place a decade ago (Byrne & Reinhart, 1990) and replicated Byrne's previous investigation published in 1982. In reporting changes that had occurred in the period between the two studies, Byrne and Reinhart noted that although psychologists did not regard the current training as optimal, there had been an increase in the level of formal qualifications held by practising clinical psychologists.…”
Section: I2amentioning
confidence: 58%
See 2 more Smart Citations
“…CBT has been adapted for a range of problems and disorders and is commonly practiced across various countries and practice contexts (A. T. Beck, ; Norcross, Sayette, & Pomerantz, ; Orlinsky et al, ). In Australia, CBT is a primary orientation identified by clinicians (Byrne & Reinhart, ; Hicks, Alexander, & Jones, ; Kazantzis & Deane, ) and is the preferred intervention for government‐funded community access to psychological services (Department of Health, ).…”
Section: Introductionmentioning
confidence: 99%